2022
DOI: 10.1111/ilr.12224
|View full text |Cite
|
Sign up to set email alerts
|

Coping with precarity during COVID‐19: A study of platform work in Poland

Abstract: This article explores how the COVID-19 pandemic has affected platform workers' work and life experiences in Poland and how they have responded. These workers have been exposed to substantial fluctuations in demand during the pandemic, magnifying the distortions existing in an unregulated asymmetr ical employment relationship that diverges from the standard employment relationship. Findings illustrate how workers have attempted to reduce the disruptions underpinning this relationship by adopting different strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The third factor affecting hourly wages is the current supply and demand for tasks and workers (Nikzad 2017 ; Bayudan-Dacuycuy and Kryz Baje 2021 ; Zhang et al 2022 ). Muszyński et al ( 2021 ) contend that the smoothing of labor supply and demand through employer–employee relationships is absent in crowdworking. Workers completing microtasks, in particular, are vulnerable to low hourly wages caused by labor oversupply, as microtasks require few skills and therefore have a low barrier to entry (Braesemann et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third factor affecting hourly wages is the current supply and demand for tasks and workers (Nikzad 2017 ; Bayudan-Dacuycuy and Kryz Baje 2021 ; Zhang et al 2022 ). Muszyński et al ( 2021 ) contend that the smoothing of labor supply and demand through employer–employee relationships is absent in crowdworking. Workers completing microtasks, in particular, are vulnerable to low hourly wages caused by labor oversupply, as microtasks require few skills and therefore have a low barrier to entry (Braesemann et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…For many crowdworkers, however, microtasks could represent a gap-filling activity that is easily carried out between other activities and which therefore also pays a comparatively low wage (Teevan 2016 ; Newlands and Lutz 2021 ). During the COVID-19 pandemic, increasingly more people turned to crowdwork as a source of income, thereby lowering average wages through increased competition and supply (Stephany et al 2020 ; Braesemann et al 2021 ; Muszyński et al 2021 ). However, even before the pandemic, Graham and Anwar ( 2019 ) identified a large oversupply of labor on one of the largest platforms for online freelancers worldwide (Kässi and Lehdonvirta 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…They emphasize increased health risks [44], and the high prevalence of infection among couriers in Ecuador [43]. They also report a global worsening of working conditions such as the intensification of precarious working conditions [6,40,63] due to greater financial insecurity [29] and reduced earnings per hour for the same number of working hours [1,44]. Finally, the pandemic helped to expose some of the vulnerability these workers were facing [49].…”
Section: Impacts Of the Pandemicmentioning
confidence: 99%
“…To understand how to interact effectively with algorithms, gig workers engage themselves in three types of activities, sense-making, circumventing, and manipulating algorithms [ 13 ]. Muszynski et al [ 30 ] have studied the impact of COVID–19 on Polish gig workers’ life and work experiences. They have shown that based on access to resources, access to institutional capabilities, and orientations, gig workers take different strategies in dealing with substantial fluctuations of demand on digital work platforms.…”
Section: Gig Economy Gig–worker Experience and Copingmentioning
confidence: 99%
“…They have shown that based on access to resources, access to institutional capabilities, and orientations, gig workers take different strategies in dealing with substantial fluctuations of demand on digital work platforms. The three coping strategies discussed in their article are (1) staying loyal and not challenging the perils of the platform; (2) hybrid strategies: staying loyal and voicing complaints; and (3) exiting [ 30 ].…”
Section: Gig Economy Gig–worker Experience and Copingmentioning
confidence: 99%